Early Childhood Education: Early Character Education: Cultivating Empathy and Discipline in Early Childhood Education Children - Dwi Suryahartati; Aceng Haetami; Masrum Masrum (Journal of Gemilang, 2025)
Early Childhood Education (PAUD) plays a strategic role in shaping the foundation of a child's complete personality, including character values such as empathy and discipline. This study aims to describe the process of instilling these values through a contextual, natural, and participatory learning approach. Using descriptive qualitative methods, this study involved teachers, principals, and parents from several PAUD institutions in Indonesia. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation studies. The results showed that the value of empathy was instilled through storytelling, role-playing, and social interactions that build children's emotional awareness, while discipline was developed through habituation, classroom rules, and a reflective approach. Furthermore, collaboration between teachers, principals, and parents proved crucial in creating a consistent character education ecosystem. This study also identified challenges in implementing character education, such as differences in children's backgrounds, limited learning media, low parental participation, and teacher readiness. The success of instilling values is greatly influenced by an understanding of social dynamics and the application of natural, developmentally appropriate learning. This study confirms that character education from an early age must be carried out holistically, adaptively, and sustainably, in order to form a generation that is empathetic, independent, and responsible.